Burning Bright - Chevalier, Tracy; HarperCollins (London : HarperCollins, 2007)
The Kellaway family, newly arrived in London in 1792 where father Thomas has been offered work by circus entrepreneur Philip Astley, discovers they are neighbors to famous printer, poet, and political radical William Blake, who is inspired by the coming-of-age adventures of young Jem Kellaway and his sister Maisie to writer one of his most famous works.
Adult
Keywords: Blake, William, -- 1757-1827 -- Fiction; Historical fiction